Proceedings of the International Conference on Business and Management Research (ICBMR-17) 2017
DOI: 10.2991/icbmr-17.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Corporate Social Responsibility, Business Diversification, and Company Size upon Company Value

Abstract: The purpose of a company is to maximize company value, which is synonymous to increasing the shareholders' wealth. There are some variables that could determine company value such as corporate social responsibility (CSR), diversification of business, and company size. This study examines the influence of corporate social responsibility (CSR), diversification of business, and size of the company upon the value of manufacturing companies listed on the Indonesian Stock Exchange (IDX). The research population is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The study done by Mangoting et al, (2019), Dao et al, (2020) & Mahrani & Soewarno (2018) stated that CSR implementation has a positive impact on a company's value creation; higher frequency of CSR activities lead to continues improvement of company value. However, another study by Masdupi & Yulius (2017) & Hafez, (2016 found a different result, suggesting that CSR has no influence on company value. Further, Crisóstomo et al, (2011) found that CSR disclosure instead has a negative impact on a company's value creation, which means higher level of CSR disclosure could decrease company value.…”
Section: Introductionmentioning
confidence: 95%
“…The study done by Mangoting et al, (2019), Dao et al, (2020) & Mahrani & Soewarno (2018) stated that CSR implementation has a positive impact on a company's value creation; higher frequency of CSR activities lead to continues improvement of company value. However, another study by Masdupi & Yulius (2017) & Hafez, (2016 found a different result, suggesting that CSR has no influence on company value. Further, Crisóstomo et al, (2011) found that CSR disclosure instead has a negative impact on a company's value creation, which means higher level of CSR disclosure could decrease company value.…”
Section: Introductionmentioning
confidence: 95%
“…Stakeholder theory explains that companies do not only focus on profits or the interests of the company itself (Masdupi & Yulius, 2017), but sustainability (Lindawati & Puspita, 2015). Stakeholder theory explains that CSR can meet stakeholder demands so that it can create a good reputation for the company (Alipour et al, 2019;Fiandrino et al, 2019;Radhouane et al, 2018;Xiao et al, 2018).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…If given a cycle, the company does not carry out business activities that are oriented only to profit but also needs to provide reciprocal benefits to stakeholders for operational sustainability (Hardi & Chairina, 2019;Masdupi & Yulius, 2017) which is following stakeholder theory (Wicks & Harrison, 2017;Zakhem & Palmer, 2017). Differences in interests between stakeholders and the company can arise as a result of the incompatibility of the company's operating activities with the expectations of stakeholders so that pressure arises from stakeholders on the company, so the purpose of corporate CSR is to mitigate a gap between them (Benn et al, 2016;Lindawati & Puspita, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations